The Role of Orgasmic Difficulty in Attributing Cause for Positive and Negative Sexual Outcomes in Women: The Importance of Cross-Cultural Analyses. Issue 4 (3rd May 2021) - Rowland, David L.; Kneusel, Julia A.; Bacys, Katelyn R.; Hamilton, Benjamin D.; Bhutto, Zainab; Zadeh, Zainab
Abstract: Studies investigating women's attributions for positive and negative sexual experiences have been slow to adopt a cross-cultural perspective, resulting in a perspective defined by Western experiences. This cross-cultural analysis examined such attribution processes in 88 Pakistani and 187 USA women, and identified differences related to orgasmic difficulty and country-of-origin. Pakistani and USA women differed on both self-blame and relationship blame related to negative sexual outcomes, an effect intensified in Pakistani women who reported orgasmic difficulty during partnered sex. Differences are interpreted within a cultural context and underscore the importance of addressing women's sexual experiences in a more global context.